Implementation of the Multiplus/Multiplix Parallel Processing Environment - Aude, Júlio S.; Meslin, Alexandre M.; Cruz, Aluisio A.; Santos, Cláudio M. P.; Bronstein, Gerson; Cota, Iuri N.; Cordeiro, Luiz F. M.; Barros, Márcio O.; João Jr., Mário; Pinto, Serafim B.; Oliveira, Sidney C. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1995: Anais do VII Simpósio Brasileiro de Arquitetura de Computadores e Processamento de Alto DesempenhoDO - 10.5753/sbac-pad.1995.19892, 1995)
The MULTIPLUS project aims at the development of a modular distributed shared memory parallel architecture able to support up to 1024 processing elements based on SPARC microprocessors and at the implementation of MULPLIX, a Unix-like operating system which provides a suitable parallel programming environment for the MULTIPLUS architecture. After reviewing the main features of the definition of the MULTIPLUS architecture and the MULPLIX operating system, this paper describes in detail the current implementation of the main modules of the MULTIPLUS architecture and presents, with an illustration example, the parallel programming primitives already implemented within MULPLIX.